Validation Method for Digital Flow Meter for Fuel Vendors - Megantoro, Prisma; Husnan, Danar Aulia; Sattar, Mian Usman; Maseleno, Andino; Tanane, Omar (Universitas Muhammadiyah Yogyakarta, 2020)
Research on the design of fuel measuring device for vendors using Arduino Mega 2560 microcontroller and positive displacement flow meter sensor was conducted. It aimed to design and create a prototype of fuel measuring device for retail traders, and to find error values on the device. The research began with searching for reference books, making hardware and programming, and finally testing the device. The components used were Arduino Mega 2560, positive displacement flow meter sensor, keypad, selenoid valve and 4x20 LCD. The test was performed by comparing the results of the measuring cup to the number displayed on the LCD, followed by reproducibility. Data collection was carried out every volume of 500ml, 1000ml, 1500ml, and 2000ml. The results of the research showed that the error value was 2.24% with the comparison of 1.91%. Several factors affecting the highness of error value were human factor, sensor and device factor, as well as the comparison device being used. Referring to the error value that smaller than 5%, this device is worthy for mass production